Synthesis and Characterization of [Fe(picolinate)3][MnNi(oxalate)3].CH3OH Polymeric Complex - Fahimah Martak; Djulia Onggo; Ismunandar Ismunandar; Agung Nugroho (Universitas Gadjah Mada, 2014)
Polymeric complex [Fe(picolinate)3][MnNi(oxalate)3].CH3OH has been successfully synthesized using H-tube technique. The chemical composition of the synthesized product was determined by Elemental Analysis and Atomic Absorption Spectrometry. Infrared spectrum shows that the oxalate ligand acts as a bridging ligand. The crystalline product exists in the form of monoclinic structure and space group P21n as shown on the pattern of X-Ray Diffraction and has a similar structure with [Fe(bpp)2][MnCr(oxalate)3] complex. The magnetic susceptibility of the polymeric complex exhibits high spin and paramagnetic behavior.